Transitivity of Try and V Construction in British and American English - Faisal Mustafa; Syamsul Bahri Yusuf (Langkawi: Journal of The Association for Arabic and English, 2021)
Try and V construction is prevalent in British and American English. This construction is found in both spoken and written English, although with different frequencies. The verb in this construction only appears in in the base form. The lack of research on this verb formation leaves many aspects unexplored, one of which is the transitivity of the verb. Therefore, this study is intended to find out the number of arguments informed by this construction by matching the number of arguments to the verb try and the verb following it after the conjunction and. Two verbs were used to test this match, i.e., give and bring, which are three-place predicate verbs, and other two two-place predicate verbs, i.e., see and answer, were used to validate the finding. British National Corpus (BNC) and Corpus of Contemporary American English (COCA) were used to collect the data. The findings show that the number of arguments matched the verb following the conjunction and. Therefore, it can be concluded the number of arguments in try and V construction is not unique to this construction, but it is similar to the try to V, where V is the non-finite verb which selects the number of arguments. This result suggests that try and V construction needs to be included in English grammar textbooks in order that non-native speakers can use and understand this rare grammatical rule in appropriate contexts.